(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Small and Medium-sized Enterprises (SMEs) play a pivotal role in the Mauritania economy, serving as a vital engine for economic growth and a primary source of employment opportunities. However, these enterprises encounter a lack of funding. Therefore, this study aimed to determine the impact of characteristics of small and medium enterprises (SMEs) and Managerial Profiles on obtaining bank financing in Mauritania. A binary logistic regression analysis method was employed, applied to a sample of 155 SMEs. The study found that the factors influencing the acquisition of funding include sector of activity, size, the manager’s professional experience and educational level.